Photoionization of Astrophysically Relevant Atomic Ions at PIPE - Stefan Schippers; Alfred Müller (Atoms, 2020)
We review recent work on the photoionization of atomic ions of astrophysical interest that has been carried out at the photon-ion merged-beams setup PIPE, a permanently installed end station at the XUV beamline P04 of the PETRA III synchrotron radiation source operated by DESY in Hamburg, Germany. Our results on single and multiple L-shell photoionization of Fe<semantics>+</semantics>, Fe<semantics>2+</semantics>, and Fe<semantics>3+</semantics> ions, and on single and multiple K-shell photoionization of C<semantics>−</semantics>, C<semantics>+</semantics>, C<semantics>4+</semantics>, Ne<semantics>+</semantics>, and Si<semantics>2+</semantics> ions are discussed in astrophysical contexts. Moreover, these experimental results bear witness of the fact that the implementation of the photon-ion merged-beams method at one of the world’s brightest synchrotron light sources has led to a breakthrough for the experimental study of atomic inner-shell photoionization processes with ions.